The Twin Deficits Phenomenon: Evidence from Pakistan (The Pakistan Development Review, 2000)
Like most developing countries a steady budget deficit in Pakistan is the primary cause of all major ills of the economy. It has varied between 5.4 to 8.7 percent during last two decades. On the other hand the current account deficit varied between 2.7 to 7.2 percent during the same period. The variations in fiscal policy can lead to predictable developments in an open economy’s performance on current account, remains a controversial issue. An important aspect of this issue concerns what is termed as twin deficit analysis, according to which fiscal deficits and current account balances are very closely related so that reductions in the former are both necessary and sufficient to obtain improved performance in the later. Theoretical work on the relationship that exist between variations in fiscal policy and the current account balance has been based upon two types of models. These models are constructed from postulated behavioural relationships that purport to describe how the economy works in aggregate without explaining the behaviour of agents who make up the economy [Mundel (1963); Branson (1976); Dornbusch (1976); Kawai (1985) and Marston (1985)]. The second type of model, derives the important macroeconomic relationships from the microfoundations of individual optimising behaviour [Dixit (1978); Neary (1980); Obstfeld (1981); Persson (1982); Kimbrough (1985); Frenkel and Razin (1986); Cuddington and Vinals (1985, 1986a) and Moore (1989)]. However, both of these approaches have yielded divergent results.